Sexual behaviour and sexual health of Australian prisoners - Butler, Tony; Malacova, E.; Richters, J.; Yap, L.; Grant, L.; Richards, A.; Smith, A.; Donovan, B. (2013)
Objective To describe prisoners' sexual experiences and sexual practices while in the community, sexual identities, and sexual health (e.g. self-reported exposure to sexually transmissible infections (STIs) and female reproductive outcomes) using data from the Sexual Health and Attitudes of Australian Prisoners (SHAAP) survey. Methods: This study used a computer-assisted telephone interview to screen randomly selected prisoners using a questionnaire based on the Australian Study of Health and Relationships survey. Results: 2351 men and women prisoners from New South Wales and Queensland took part in the survey. Most men identified as heterosexual (95.7%) and reported sexual attraction (91.0%) and sexual experiences (86.6%) only with the opposite sex, but 28.5% of women prisoners identified as bisexual. Sexual attraction correlated with sexual experience (men: r=0.63; women: r=0.84) more than with sexual identity (men: r=0.53; women: r=0.54). Male prisoners reported more lifetime opposite-sex partners than women prisoners (median 24 v. 10). Women prisoners were more likely than men to report a prior STI (35.1% v. 20.0%). Conclusions: Prisoners are a high-risk group with regard to sexual health. There is a need for a better understanding of the sexual health of this population group so that education campaigns and interventions specific to this population group can be developed. © 2013 CSIRO.